PRODUKSI MAKNA DALAM MEDIA SOSIAL: PERSPEKTIF ANTROPOLOGI POSTMODERN - Fauziah; Nur Ika Sari; Nurul Musrifah (STKIP Subang, 2026)
The development of digital technology has transformed the way people interact, communicate, and construct meaning in social contexts. Social media is now more than just a communication tool, but has transformed into a cultural space where individuals can create, duplicate, and negotiate meaning dynamically. The purpose of this research is to analyze how meaning is produced on social media using a postmodern anthropological perspective. The methodology applied is a qualitative approach with descriptive-analytical analysis grounded in literature review and an appreciation of digital cultural phenomena. The research findings reveal that the process of meaning production on social media occurs through symbolic interactions between users, who function as both producers and consumers (prosumers). Meaning itself is not fixed, but rather is formed through a process of encoding by content creators and decoding by audiences, influenced by social backgrounds, culture, and personal experiences. From a postmodern anthropological perspective, reality on social media is fluid, variable, and devoid of a single, absolute truth. The phenomena of simulacra and hyperreality demonstrate that the boundaries between reality and digital representation are often blurred, leading to virtual reality being perceived as superior to actual reality. Furthermore, this study emphasizes the multiplicity of meanings in social media, where a single piece of content can be interpreted differently by many individuals. This suggests that social media functions as a discursive arena that allows for diverse interpretations without any governing authority. In this way, social media can be viewed as a complex cultural space in digital society, where meaning, identity, and reality are constantly created and negotiated.